Digital Wellbeing at Scale: Global Assessment of Stress, Productivity, and Burnout in Hybrid Organizations - Sumarno, Ahmad Agus; Yona, Mira; Ariyati, Yannik; Siregar, Hanafi; Ellysiana, Nur (Journal of Economics and Management Scienties, 2026)
This study provides a comprehensive assessment of digital wellbeing in hybrid organizations by examining how digital stress, productivity, and burnout interact across diverse workplace contexts in Batam, Medan, and Kuala Lumpur. The research employs a quantitative design using SmartPLS to evaluate both the measurement and structural models, drawing on responses from 912 employees working within digitally mediated environments. The findings reveal that digital stress is predominantly driven by communication overload, high platform switching frequency, and prolonged screen exposure, conditions that collectively elevate cognitive strain and disrupt workflow continuity. The structural model demonstrates that digital stress has a significant negative impact on productivity, while simultaneously exerting a strong positive influence on burnout. Productivity, on the other hand, contributes to lowering emotional exhaustion, indicating its moderating role within the digital wellbeing framework. Regional comparisons further show that employees in technologically mature ecosystems, such as Kuala Lumpur, experience lower digital strain and greater productivity stability compared to those in Batam and Medan, where digital infrastructures and workflow standardization are less developed. These insights highlight the critical need for organizations to implement structured digital governance practices, optimize communication flows, and establish clear boundaries for virtual interaction to protect employee wellbeing. The study contributes significant empirical evidence for the development of integrated digital wellbeing strategies that support sustainable performance in hybrid work environments and offers a foundational reference for future research on digital labor dynamics.